Racializing "Oriental" Manliness: From Colonial Contexts to Cologne. Issue 1 (1st October 2017) - Zuher Jazmati; Nina Studer
Abstract : We propose a co-authored, interdisciplinary paper examining the durability of Islamophobic stereotypes connected to men from the MENA region and their specific forms of "manliness". We argue that European notions of "Oriental" manliness — covering all ethnic and religious groups from this region — were strangely homogenized and static: the colonized "Oriental" manliness was constructed as the "primitive" counterpart to an idealized form of European masculinity. The significant markers of "Oriental" manliness, as defined in the 19th century, were still essentially the same in the 1960s, when Frantz Fanon wrote that his contemporaries had solidified (but not founded) the idea of North African men as "born slackers, born liars, born thieves, born criminals". 1 The events in Cologne on New Year's Eve 2015 went viral worldwide. Right-wing groups felt vindicated when the public discourse seemed to confirm their narrative of North African, sexually uncontrolled men. A lot of the media coverage following the events in Cologne overlapped with right-wing (and colonial) notions of wild North African men, who are in Europe in order to sexually threaten the white female body. Following the assaults in Cologne, this anxiety was not just limited to women in Germany, but extended across much of Europe. To analyze this alleged durability, we propose to divide our paper into a historical part, which will give a short overview over the formulaic metaphors, images and knowledge production of colonized "Oriental" manliness. In our contemporary analyses, we will trace the harmful longevity of these colonial stereotypes, from the Victorian epoch to the sensationalist reports following the recent incidents in Cologne. We will use pictures from German (and other European) public media depicting the incidents in Cologne and analyze how they reproduced the longstanding anti-Muslim-racist stereotypical image of and knowledge on the North African masculine subject.